Post-discharge telephonic follow-up of pediatric patients affected by SARS-CoV2 infection in a single Italianpediatric COVID center: a safe and feasible way to monitor children after hospitalization - Vitangelo Clemente; Costanza Tripiciano; Patrizio Moras; Daniele Deriu; Martina Di Giuseppe; Anna Lucia Piscitelli; Michela Cammerata; Maria Antonietta De Ioris; Francesca Ippolita Calò Carducci; Stefania Bernardi; Andrea Campana; Patrizia D'Argenio; et al. (BMC, 2021)
Abstract Background SARS-CoV-2 infection in children is often non severe and in the majority of cases does not require long term hospitalization, nevertheless it is burdened with social issues and managing difficulties. To our knowledge there is no literature on telephonic follow up in pediatric patients with positive PCR for SARS-CoV-2 on rhino-pharyngeal swab after discharge. The aim of the study is to describe our experience in a telephonic follow up which can allow early and safe discharge from hospital while keeping the patients under close clinical monitoring. Materials and methods Sixty-five children were admitted for SARS-CoV-2 infection at Bambino Gesù Pediatric Hospital COVID Center from 16th March to 3rd July. We monitored through a telephonic follow-up, using a specific survey, the patients discharged still presenting a positive PCR for SARS-CoV-2. We checked if any symptoms occurred at home until recovery, defined as two consecutive negative PCR for SARS-CoV-2 on rhino-pharyngeal swabs. Results During the follow up 7 patients had mild and self-limited symptoms related to SARS-CoV-2 infection, while 2 patients were re-hospitalized. One patient had Multisystem Inflammatory Syndrome in Children (MIS-C), the other patient had an increase in troponin and D-dimers. We also monitored the average time of viral shedding, resulting in a median duration of 28 days. Conclusion Our experience describes the daily telephonic follow up as safe in pediatric patients discharged with positive PCR. As a matter of fact it could avoid long term hospitalization and allow to promptly re-hospitalize children with major complications such as MIS-C.